Rasch Model Validation of Critical Thinking Assessment in Elementary Education: Validasi Instrumen Penilaian Berpikir Kritis Siswa Sekolah Dasar Berbasis Rasch - Purnamasari, Rika; Maftuh, Bunyamin; Hidayat, Mupid; Warlim, Warlim; Dahliyana, Asep; Ruyadi, Yadi; Nurdin, Encep Syarief; Fauziah, Nurul (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The digital era requires elementary school students to possess critical thinking as a foundational character to evaluate information and make reasoned decisions within learning processes. Specific Background: Project-based learning integrated with STEAM has been positioned as a relevant pedagogical context for fostering critical thinking, yet systematic assessment remains challenging at the elementary level. Knowledge Gap: Existing assessment instruments are predominantly conventional and lack robust psychometric validation to comprehensively measure critical thinking characteristics in STEAM-oriented project learning. Aims: This study aims to validate a critical thinking character assessment instrument for elementary school students using Rasch Model analysis within project-based STEAM learning in the digital era. Results: From 29 developed items, 20 items met Rasch validity criteria, with person reliability of 0.82, item reliability of 0.98, and a Cronbach’s Alpha value of 0.81, indicating strong internal consistency and effective differentiation of student ability levels. Novelty: This study presents a psychometrically validated instrument specifically designed to assess critical thinking character in elementary school students through STEAM-based project learning using Rasch Model analysis. Implications: The validated instrument provides teachers with an objective and systematic assessment tool to monitor and develop students’ critical thinking character in alignment with the demands of digital-era elementary education. Highlights • The instrument demonstrated high person and item reliability through Rasch analysis• Valid items represented five dimensions of critical thinking character• Assessment results supported objective differentiation of student ability levels Keywords Critical Thinking; Rasch Model; Project Based Learning; STEAM Education; Elementary School